Production systems and water productivity in the Nile Basin - Karimi, P.; Notenbaert, An Maria Omer; Breugel, P. van; Molden, David J. (IWMI/ILRI, 2009)
This poster shows the production systems within the Nile basin, livestock–water productivity in agricultural systems, water productivity variation and the aquaculture production in the Nile basin countries. It also states the scope for the improvements.